2022
DOI: 10.1515/hf-2022-0107
|View full text |Cite
|
Sign up to set email alerts
|

The influence of vacuum heat treatment on the pore structure of earlywood and latewood of larch

Abstract: To investigate the changes in the pore structure of earlywood and latewood (EW and LW) in larch during the heat treatment process, this study applied nitrogen adsorption and mercury intrusion porosimetry (MIP) to measure wood pore characteristics. Wood samples were heat treated within a vacuum atmosphere at temperatures between 180 and 220 °C for 6 h. Analysis conducted on nitrogen adsorption isotherms indicated that the micropores and mesopores in the cell walls were present in both untreated and heat-treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The freeze-dried TrW samples showed enhanced adsorption in the micro and mesoporous region [Supplementary Figure 1C and D], and a characteristic sharp step-down in the desorption curve is called "cavitation" -a sign of a significant level of micro-and mesoporosity [21,22] . All samples showed H4-type hysteresis loops with non-limiting adsorption at high relative pressure [23] . The distribution of loops over a wide relative pressure range proves the presence of pores with varied diameters in wood.…”
Section: Wood Modification and Characterizationmentioning
confidence: 97%
“…The freeze-dried TrW samples showed enhanced adsorption in the micro and mesoporous region [Supplementary Figure 1C and D], and a characteristic sharp step-down in the desorption curve is called "cavitation" -a sign of a significant level of micro-and mesoporosity [21,22] . All samples showed H4-type hysteresis loops with non-limiting adsorption at high relative pressure [23] . The distribution of loops over a wide relative pressure range proves the presence of pores with varied diameters in wood.…”
Section: Wood Modification and Characterizationmentioning
confidence: 97%
“…This was partly inconsistent with the results reported by Liu et al ( 2023), who claimed that the S BET and V total were both decreased no matter in saturated steam or in air condition at 180 and 210°C. However, Sun et al (2022) found that the porosity of thermally modi ed pine rst increased and then decreased with the increasing modi cation temperature, indicating the change of porosity was related with the intensity of TM. Higher modi cation temperature and leaching post-treatment mostly induced an increase in porosity, however, the higher TM temperature also resulted in a decrease in the average mesopore diameter.…”
Section: Nitrogen Adsorption Analysismentioning
confidence: 97%
“…TM results in weight loss (Czajkowski et al 2020), changes in mechanical strength, and reduction in equilibrium moisture content (EMC) and hygroscopicity, which subsequently improves the dimensional stability (Borůvka et al 2019) and decay resistance (Cao et al 2011). These property changes mainly deriving from the degardation of chemical constituent (hemicellulose, cellulose, and lignin) ) and changes of pore structure (Sun et al 2022). During TM process, the decrease of -OH groups (Xu et al 2022) due to the degradation of hydrophilic hemicellulose, and the increase of relative crystallinity (Andersson et al 2005) due to the reduced amorphous cellulose would decrease the hygroscopicity of thermally modi ed wood (TMW).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation